The efficacy of Origanum majorana nanocubosomal systems in ameliorating submandibular salivary gland alterations in streptozotocin-induced diabetic rats - Dina B. E. Farag; Carol Yousry; Abdulaziz Mohsen Al-Mahallawi; Hesham I. El-Askary; Meselhy R. Meselhy; Nermeen AbuBakr (Taylor & Francis Group, 2022)
Diabetes mellitus is a challenging health problem. Salivary gland dysfunction is one of its complications. Current treatments possess numerous adverse effects. Therefore, herbal extracts have emerged as a promising approach for safe and effective treatment. However, they are required in large doses to achieve the desired effect. Accordingly, Origanum majorana extract (OE) was incorporated into nano-sized systems to enhance its biological effects at lower dosages. OE was standardized against rosmarinic acid (RA) and then loaded into nano-cubosomal (NC) systems via a 23 full-factorial design. Two optimum nano-systems at different drug loads (2.08 or 1.04 mg-RA/mL) were selected and assessed in vivo to compare their effects in streptozotocin-induced diabetic rats against conventional OE (2.08 mg-RA/mL). Blood glucose was evaluated weekly. Submandibular salivary glands were processed for histopathological examination and nuclear factor-erythroid 2-related factor 2 (Nrf2), Kelch-like ECH-associated protein 1 (Keap1), and p38-MAPK gene expression analysis. NC systems were successfully prepared and optimized where the optimum systems showed nano-sized vesicles (210.4-368.3 nm) and high zeta potential values. In vivo results showed a significant lower blood glucose in all treated groups, with an exceptional reduction with NC formulations. Marked histopathological improvement was observed in all OE-treated groups, with OE-NC4 (2.08 mg-RA/mL) demonstrating the best features. This was supported by RT-PCR; where the OE-NC4 group recorded the highest mean value of Nrf2 and the least mean values of Keap1 and p38-MAPK, followed by OE-NC3 and OE groups. In conclusion, OE-loaded NC enhanced the anti-hyperglycemic effect of OE and ameliorated diabetic gland alterations compared to conventional OE. Thus, cubosomal nano-systems could be anticipated as potential carriers for the best outcome with OE.